Managing type 1 diabetes during the COVID-19 pandemic is a team effort: a qualitative study of the experiences of young people and their parents. Issue 1 (10th November 2021) - Parkinson, Anne; Brew-Sam, Nicola; Hall Dykgraaf, Sally; Nolan, Christopher; Lafferty, Antony; Schmidli, Robert; Brown, Ellen; Brown, Karen; Pedley, Lachlan; Ebbeck, Harry; Pedley, Elizabeth; Wright, Kristine; et al.
Abstract : Objective: To explore the experiences of young people with type 1 diabetes mellitus (T1DM) and their parents in accessing integrated family-centred care in the Australian Capital Territory during the COVID-19 pandemic. Methods and analysis: This is a pragmatic, qualitative descriptive study for which we conducted semistructured interviews with 11 young people with T1DM aged 12–16 years and 10 of their parents who attended an outpatient diabetes service in Canberra, Australia. Thematic analysis was conducted in accordance with the methods outlined by Braun and Clarke. Results: Three themes were identified: feeling vulnerable, new ways of accessing care and trust in the interdisciplinary diabetes healthcare team. Participants believed having T1DM made them more vulnerable to poor outcomes if they contracted COVID-19, resulting in avoidance of face-to-face care. Telephone consultations offered a convenient and contact-free way to undertake 3-monthly reviews. The greatest difference between telephone and face-to-face consultations was not having access to the whole interdisciplinary diabetes support team at one appointment, physical examination and haemoglobin A1c testing during telehealth consultations. Participants trusted that clinicians would arrange face-to-face meetings if required. Some felt a video option might be better than telephone, reflecting in part the need for more training in communication skills for remote consultations. Conclusion: Young people with T1DM and their parents require collaborative care and contact with multiple healthcare professionals to facilitate self-management and glycaemic control. While telephone consultations offered convenient, safe, contact-free access to healthcare professionals during the COVID-19 pandemic, the added value of video consultations and facilitating access to the whole interdisciplinary diabetes support team need to be considered in future clinical implementation of telehealth.